Analisis Pengaruh Cognitive Load dan Fatigue Learning terhadap Keberhasilan Siswa dalam Menyelesaikan Soal Higher-Order Thinking Skills (HOTS): Analysis of the Influence of Cognitive Load and Fatigue Learning on Student Success in Solving Higher-Order Thinking Skills (HOTS) Problems - Marlen Wariunsora; Megawati Beddu; Nuryati Nuryati; Ulfah Sa'adah; Almira Ulimaz; Bernadin Maria Noenoek Februati (ITScience (Information Technology and Science), 2024)
This study aims to analyze the effect of cognitive load and learning fatigue on students' success in solving Higher-Order Thinking Skills (HOTS) questions. Mental fatigue due to extensive and rigorous learning is known as learning fatigue, while cognitive load refers to the mental stress experienced by students when absorbing new material. This study used an experimental and quantitative technique. For this study, 120 students were used, half in the control group and the other half in the experimental group. Data were collected through cognitive load surveys, HOTS tests, and learning fatigue. The study's findings showed a correlation between cognitive load and students' performance on the HOTS test. Critical thinking and analytical skills, essential for answering HOTS questions, were often lacking in students with high cognitive load. Another factor that decreased students' efficacy in solving problems was learning fatigue. When students do not get enough sleep or do not spend enough time studying, they become mentally exhausted and lose focus more easily. This fatigue reduces their ability to persist in working on challenging tasks. As a result, students have difficulty applying their information in a higher and more integrated context, even though their knowledge is quite good. The importance of effectively managing cognitive load and learning regarding students' effectiveness in solving HOTS problems cannot be overstated.